Temporal coordination of simulated timed trajectories for two vision-guided vehicles - Santos, Cristina (2006)
We present an attractor based dynamics that autonomously generates temporally discrete movements and temporally coordinated movements for two vehicles, stably adapted to changing online sensory information. Movement termination is entirely sensor driven. We build on a previously proposed solution in which timed trajectories and sequences of movements were generated as attractor solutions of dynamic systems. We present a novel system composed of two coupled dynamical architectures that temporally coordinate the solutions of these dynamical systems. The coupled dynamics enable synchronization of the different components providing an independence relatively to the specification of their individual parameters. We apply this architecture to generate temporally coordinated trajectories for two vision-guided mobile robots in a simulated environment, whose goal is to reach a target in an approximately constant time while navigating within a non-structured environment. The results illustrate the robustness of the proposed decisionmaking mechanism and show that the two vehicles are temporal coordinated: they terminate their movements approximately simultaneously.